Enhancing Zakat Management: The Role of Monitoring and Evaluation in the Amil Zakat Agency - Arno, Abd Kadir; Mujahidin, Mujahidin (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractCompliance with basic principles such as financial transparency and accountability is needed to manage zakat. Transparency in reporting zakat management will increase Muzakki's trust so that Zakat's receipts will eventually grow. This article analyzes the monitoring and evaluation of zakat management at the amil zakat board of Palopo City. It focuses on financial, management, and quality audits (planning, collection, distribution, administration) and internal compliance audits. The study assesses the performance of these areas by using importance-performance analysis. The findings suggest prioritizing financial audits is crucial for building Muzakki's trust. Additionally, enforcing management audits, planning quality audits, finance, reporting, and internal compliance audits are essential for effective zakat management. Keywords:Evaluation, Importance Performance Analysis, Monitoring, Zakat Management